Juridical and Socio-Cultural Analysis of Inheritance Distribution Under the Customary Law System of the Dayak Community in Indramayu - Busthomi, Achmad Otong; Jaelani, Aan; Setyawan, Edy; Abadi, Khafid; Syam, Roqiyul Ma’arif (UIN K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the inheritance distribution system within the Dayak community in Indramayu using a juridical-socio-cultural approach. The research employs a qualitative-descriptive method, integrating the analysis of positive law and customary law with local socio-cultural values specific to the community’s unique context. Data were collected through field observations, document studies, and semi-structured interviews with customary leaders and members of the Dayak community. The data analysis technique is based on the interactive model of Miles and Huberman and utilizes a normative-juridical and cultural-interpretive approach to explore the ongoing dynamics. The findings reveal that the bilateral kinship structure and customary principles such as Sejarah Alam Ngaji Rasa (the natural history of internal reflection), Menyatu dengan Alam (oneness with nature), and Ngaula Ning Anak Rabi (dedication to one's offspring and their spouses) influence an egalitarian inheritance system, although variations exist among subgroups. However, within the framework of legal pluralism and distributive justice, the system still reflects disparities, particularly concerning the rights of women and adopted children in matters of inheritance. The study recommends reformulating customary law to be more responsive to contemporary social justice values and to ensure the principles of non-discrimination and equality in the inheritance distribution process.